Implementing a New Tool to Predict the Risk of Intimate Partner Violence in Rural China - Hou, Fengsu (Journal of interpersonal violence, 2021)
Most of current scales for assessing intimate partner violence (IPV) were developed for Western populations. The Chinese Risk Assessment Tool for Victims (CRAT-V) was a new scale evaluating the risk of IPV, which was developed based on Chinese populations in the context of Chinese culture. To determine whether the CRAT-V could add further value to research involving IPV and violence against women in rural China, we sought to implement the CRAT-V and to explore its factor structure among a rural population in the mainland of China. This study included women from rural Sichuan Province of China, who aged 16 years and older, had been living locally for at least 2 years, and reported that they were married or in a relationship in the preceding year. A total of 670 participants completed the CRAT-V during the field survey. We utilized exploratory factor analysis to validate the fact structure of CRAT-V. The Cronbach’s alpha of the CRAT-V was 0.90, indicating good reliability. The CRAT-V reported that 45.07% (302/670) of participants were in risk of IPV, and the risk was higher in women who were 16 to 29 years old, having 7 years and higher education, and living in stem families. The CRAT-V fit a 5-factor model including healthy relationship, jealous feeling, jealous reaction, stressful living condition, and sexual abuse. Our findings provided support for using the CRAT-V as a culturally sensitive measure to predict the risk of experiencing IPV in China, and lend insights into factors that may contribute to timely IPV prevention and intervention.